1994
DOI: 10.1177/019262339402200406
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity in Guinea Pigs Following Acute Inhalation Exposure to 1,1-Dichloro-2,2,2-Trifluoroethane

Abstract: or DDT may be considered from the difference between the effects of PB (l, 2, 8, 12, 33). On the other hand, retinoic acid inhibits the junctional communication between a variety of vertebrate cell types in culture (20, 35) and acts synergistically with a promoter to block intercellular communication ( 15, 22, 25). As various natural or synthetic retinoids have been introduced, the structure-activity relationship is becoming clearer (6, 9, 27, 28, 34 by a common mechanism of toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…The fact that such correlations were not found in our previous study (Hoet et al 2001) might be explained by the narrower range of CMR values in that previous experiment, which did not include an induction protocol. Thus, the present study reports, for the first time, that differences in CYP2E1 activity may explain the notable variability in the response of the guinea-pig to HCFC-123 as reported previously by us (Hoet et al 2001) and others (Marit et al 1994;Lind Fig. 6 Centrilobular vacuolisation and necrosis of the intermediate zone of liver in a guinea-pig exposed to 5000 ppm HCFC-123 after 5% ethanol consumption (paraffin section stained with haematoxylin and eosin) Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The fact that such correlations were not found in our previous study (Hoet et al 2001) might be explained by the narrower range of CMR values in that previous experiment, which did not include an induction protocol. Thus, the present study reports, for the first time, that differences in CYP2E1 activity may explain the notable variability in the response of the guinea-pig to HCFC-123 as reported previously by us (Hoet et al 2001) and others (Marit et al 1994;Lind Fig. 6 Centrilobular vacuolisation and necrosis of the intermediate zone of liver in a guinea-pig exposed to 5000 ppm HCFC-123 after 5% ethanol consumption (paraffin section stained with haematoxylin and eosin) Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Acute inhalation of HCFC-123 has also been found to produce hepatotoxicity in guinea-pigs (Marit et al 1994;Lind et al 1995;Hoet et al 2001). We recently reported that co-exposure to HCFC-124 does not significantly modify the hepatoxic potential of HCFC-123 (5000 ppm) in the guinea-pig (Hoet et al 2001).…”
Section: Introductionmentioning
confidence: 94%
“…1 Acute exposure to HCFC-123 has been shown to produce severe hepatotoxicity in guinea pigs. 2 A single acute exposure to 1000 ppm of HCFC-123 for 4 hours can cause increases in aspartate aminotransferase and alanine aminotransferase levels compatible with hepatocellular necrosis. Increased liver weight, focal liver necrosis, induction of peroxisomal activity and hepatocellular adenomas have been found in subchronic studies in rats and dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the liver damage and necrosis observed in animals (Marit et al 1994) and man (Hoet et al 1997;Takebayashi et al 1998), following acute or repeated exposure to HCFC-123, resemble those induced by its structural and metabolic analogue, the anaesthetic halothane. Tomasi et al (1983) demonstrated activation of halothane to free radicals, accompanied by cytotoxicity, in isolated rat hepatocytes under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%